Tuberculosis Knowledge among University Students in Indonesia - Miftahul Falah; Chun-Yi Tai; Yu-Ying Lu; Chieh-Yu Liu; Lilis Lismayanti (South East Asia Nursing Research, 2019)
The rising tuberculosis (TB) incidence has become one of the main health issues in the world. The objective of this study is to understand TB knowledge and what factors may predict students’ TB knowledge among University students in Indonesia. This study included a total of 200 students. Convenient sampling was used to recruit students for the study. Univariate analysis utilized, such as t-test and one-way ANOVA and Pearson correlations coefficient. Stepwise multiple regression analysis was used to understand which factors can predict the TB knowledge. Overall, the mean score for TB knowledge among the students was 9.49 out of 14. Most of the respondents were male, and included several ethnicities, such as Sunda and non-Sunda. The variables associated with TB knowledge were gender, education, major field of study, and heard of TB. Moreover, the study found that, as predictors, the variables that influenced knowledge about TB ranked according to relevance were: major field of study and educational background. Health promotion among students is very important to improve their knowledge related to TB disease. The findings could be used for designing the university strategic programs in measuring the knowledge of TB among their students. Students with accurate knowledge of TB can help reduce its prevalence in Indonesia.